The power flap: streamlining the PMMC for consistent surgical outcomes - Maddu, Sasikanth (International Surgery Journal, 2025)
Background: The gold standard for reconstructive surgery is free flap reconstruction. Nevertheless, in developing nations, the high volume of cases, along with infrastructural and resource limitations, has led to the continued use of pectoralis major musculocutaneous flap (PMMC). This article seeks to share our experiences with the harvesting of PMMC flap and the associated outcomes. Methods: A total of 45 patients were retrospectively assessed for reconstruction over a period of 5 years (January 2019 to February 2024). Of these, 30 patients underwent reconstruction using the PMMC flap following a stream lined protocol. The outcomes of the reconstruction, categorized as either successful or unsuccessful, along with any complications that arose, were thoroughly evaluated. Data was analyzed using SPSS version 26.0.and presented a numbers and percentages. Results: The largest proportion of patients fell within the 41–60 age range, accounting for 63.33%. The buccal mucosa was identified as the most frequent location for primary lesions, affecting 21 patients (70.00%). Among the 30 patients who received PMMC flap reconstruction following a standardized technique making it a streamlined protocol, there were no instances of complete flap loss, resulting in a success rate of 100%. However, one case did report necrosis of the breast mound where standardization was not considered. Conclusions: Based on our experience, PMMC flap remains a practical choice for reconstruction, particularly in settings with limited resources. Present approach was standardized by clearly defining the steps of the flap elevation by making it thin and less bulky, increasing its reach, minimizing the donor site morbidities and reducing the donor site deformities. With this stream lined protocol even a junior most plastic surgeon can perform the surgery confidently without facing significant complexity.